EDUKASI AKUNTANSI SEDERHANA UNTUK PEKERJA HARIAN LEPAS SEBAGAI PERWUJUDAN EKONOMI KREATIF DI SAAT PANDEMI COVID-19 - Istianingsih Sastrodiharjo; Robertus Suraji; Tri Widyastuti; Maidani (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
The purpose of this activity is to increase the understanding of casual daily workers on Simple Accounting skills regarding finances, so that they can make better planning and financial records. So that it can improve the ability to plan and record finances, increase understanding and knowledge about the importance of managing finances well. And in the end it can develop its business activities, and make its business continuity so that it can sustainably survive and grow. The implementation method used is by way of lectures, discussions and tutorials on practical questions. The material provided includes a discussion of: I. Introduction to Business Financial Management which includes; 1.) Benefits of Performing Business Financial Management - Scope of Business Financial Management Activities, 2.) Benefits of Calculation of Business Capital - Elements that are Calculated in Calculation of Business Capital Requirements - Capital Sources - Access to Capital - Types of Capital, and 3.) Benefits of Bookkeeping For Micro Business Activities - Bookkeeping & Bookkeeping Principles - Financial Bookkeeping Tools.Keywords : Simple Accounting Education, Freelancing Daily Workers, Embodiment of the Creative Economy, and the COVID-19 Pandemic.